Morning based strength training improves afternoon physical performance in rugby union players - Cook, C. J.; Kilduff, L. P.; Crewther, B. T.; Beaven, M.; West, D. J. (Journal of Science and Medicine in Sport, 2014)
Objectives: To determine if a morning training session could alter afternoon physical performance. Moreover, as testosterone (T) and cortisol (C) concentrations are significant predictors of physical performance, and both show circadian declines across the day, we examined the effects of morning training on diurnal T and C responses. Design: Eighteen semi-professional rugby union players completed this randomised and counter-balanced study. Methods: Following morning saliva collection (0900 h), players completed a control (rested), Sprint (5 × 40 m) or Weights (3 repetition-maximum [RM] bench press and squat) trial. In the afternoon (15:00 h) of each trial, a further saliva sample was collected before players completed a performance test (3RM back squat and bench press, 40 m sprint, countermovement jump [CMJ]). Results: Salivary T concentrations declined from am to pm under Control and Sprint, but not under Weights. Delta T, from am to pm, was greater under Control (-10.9 ± 2.4 pg ml-1) compared to Sprints (-6.2 ± 7.1 pg ml-1) and Weights (-1.2 ± 5.5 pg ml-1) (p ? 0.001). Delta C, from am to pm, was greater under Control compared to both Sprint and Weights (p < 0.05). Players elicited better CMJ peak power, 40-m time, 3RM bench and squat performance under Weights compared with Control and Sprint (p < 0.05). Faster 40-m times were seen under Sprint, when compared to Control (p < 0.05). Conclusions: Performing morning strength training is associated with improved physical performance in the afternoon. Additionally, the circadian decline in T concentrations appeared offset by morning training. However, it is unclear if T concentrations are, in part, causal of these improved responses or simply a reflective marker.